Penataan Perizinan dalam Gerakan Nasional Penyelamatan Sumber Daya Alam di Indonesia - Tresya, Dewi; Mayasari, Ima; Suhendra, Abdul Aziz (Integritas : Jurnal Antikorupsi, 2019)
The National Movement to Save Natural Resources is a joint program of ministries and institutions related to natural resources in Indonesia. This program was initiated, coordinated, and supervised by the Corruption Eradication Commission (CEC) as part of corruption prevention programs. In the National Movement to Save Natural Resources, licensing reform is one of the program priorities. This paper is the result of evaluative research; data were collected through literature study as well as interviews and discussions with relevant stakeholders. This paper is intended to report the progress of the licensing reform program as well as to formulate lessons learned and recommendations for the future.